Implementing cognitive diagnostic assessment training to improve middle school science teachers’ assessment practices in Lima Puluh Kota regency - Widia Kemala Sari; Selma Riyasni; Rani Oktavia (Transformasi: Jurnal Pengabdian Masyarakat, 2025)
[Bahasa]: Asesmen diagnostik berfungsi mengidentifikasi kebutuhan belajar siswa secara tepat. Namun, guru-guru di Kabupaten Lima Puluh Kota masih menghadapi kendala dalam perancangannya. Tujuan kegiatan pengabdian ini adalah meningkatkan kompetensi guru IPA dalam menyusun asesmen diagnostik kognitif sehingga mereka mampu mengidentifikasi kebutuhan belajar siswa secara lebih akurat dan komprehensif. Pengabdian menggunakan metode PAR (Participatory Action Research) dengan kegiatan pelatihan terdiri dari beberapa materi yaitu: (1) Pengenalan Anderson Krathwohl Taxonomy (AKT) dan 24 Kotak Proses Berpikir, (2) Penyusunan ATP dengan AKT menggunakan Scaffolding; dan (3) Diagnosis keterampilan kognitif siswa dilakukan menggunakan teknik Linear Extrapolation (LE), yaitu metode statistik sederhana untuk memperkirakan level kognitif berdasarkan data yang tersedia. Data kegiatan pengabdian dikumpulkan dari tiga instrumen: 1) Angket respon kegiatan; Hasil angket menunjukkan tingkat kepuasan yang tinggi terhadap kegiatan, dengan 97% responden menyatakan tanggapan positif dan 3% bersikap netral. 2) Angket persepsi kemampuan diagnostik; mayoritas guru menilai dirinya memiliki kemampuan diagnostik yang tinggi, namun masih menunjukkan kebutuhan akan penguatan dalam aspek teknologi asesmen. Analisis gender dan profesionalitas guru secara statistik dengan uji-t menunjukkan tidak ada perbedaan yang signifikan. 3) Pretest dan Posttest; terjadi peningkatan pemahaman guru sebesar 29%, dari rerata skor 84,5 menjadi 118,5 dalam penyusunan asesmen diagnostik. Temuan ini menunjukkan bahwa pelatihan berbasis PAR efektif dalam meningkatkan keterampilan diagnostik guru, terutama dalam merancang asesmen kognitif berbasis taksonomi berpikir. Kata Kunci: asesmen diagnostik, guru IPA, Participatory Action Research (PAR), scaffolding [English]: Diagnostic assessment functions to identify students’ learning needs accurately. However, teachers in Lima Puluh Kota Regency still face challenges in designing such assessments. This community service activity aims to enhance science teachers' competence in developing cognitive diagnostic assessments to more accurately and comprehensively identify students’ learning needs. The program employed the Participatory Action Research (PAR) method, with training activities consisting of several components: (1) an introduction to the Anderson–Krathwohl Taxonomy (AKT) and the 24 cognitive process cells; (2) the development of Learning Objective Flow (ATP) based on AKT using a scaffolding approach; and (3) the diagnosis of students’ cognitive skills using the Linear Extrapolation (LE) technique, a simple statistical method for estimating cognitive levels based on available data. Data from the community service activities were collected using three instruments: (1) an activity response questionnaire, the results of which showed a high level of satisfaction, with 97% of respondents expressing positive responses and 3% remaining neutral; (2) a diagnostic ability perception questionnaire, in which most teachers rated their diagnostic ability as high but still indicated a need for strengthening assessment-related technological aspects. Statistical analysis of gender and teacher professionalism using a t-test showed no significant differences; and (3) pretest and posttest results, which indicated a 29% increase in teachers’ understanding, with the average score rising from 84.5 to 118.5 in the development of diagnostic assessments. These findings demonstrate that PAR-based training is efficacious in improving teachers’ diagnostic skills, particularly in designing cognitive assessments based on thinking taxonomies. Keywords: diagnostic assessment, science teachers, Participatory Action Research (PAR), scaffolding